Lead and manganese accumulation on leaves of road side plants from Mauripor to Hawks Bay road, Karachi, Pakistan (Bangladesh Journal of Botany, 2018)
In order to investigate the heavy metals accumulation and their effects on roadside trees Conocarpus erectus. The total content of Pb and Mn was determined using atomic absorption spectrophotometry was conducted. Average concentration 10.578 ± 3.48 μg/gm of Pb and 91.98 ± 30.03 μg/gm of Mn was found. Moreover, there were variations in the level of both these heavy metals in different samples of Conocarpus tree that were collected from different locations along the road side due to different level of exposure to Pb and Mn. This physiological response of Conocarpus plant towards Pb and Mn suggests that roadside plants are good indicators of heavy metals accumulation and their subsequent effects on the environment.